Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Empiris Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Arsyi Zahwa; Nela Safelia; Rico Wijaya Z (Magister Ilmu Akuntansi Universitas Jambi, 2023)
This study aims to determine the influence of independent board of commissioners, board of commissioners, audit committee variables on company value with company size as a moderation variable (empirical study of the banking sector listed on the Indonesian stock exchange in 2019-2021). The subject studied in this study is the banking sector listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used was purposive sampling and obtained as many as 4 0 companies as samples from a total population of 43 companies. The observation period in this study is for 3 years, namely from 2019-2021 so that a total of 120 data were obtained. Data processing using WarpPls 7.0 software. This research proves that the audit committee has a positive effect on company value and company size moderates the influence of the size of the board of commissioners on the value of the company, while the independent board of commissioners, the size of the board of commissioners does not have a positive effect on Company value and company size do not moderate the influence of independent boards of commissioners and audit committees on company value.